Canine polarized macrophages express distinct functional and transcriptomic profiles - Chow, Lyndah; Soontararak, Sirikul; Wheat, William; Ammons, Dylan; Dow, Steven (Frontiers in Veterinary Science, 2022)
Macrophage differentiation and function in disease states is highly regulated by the local microenvironment. For example, macrophage exposure to IFN-g initiates the development of inflammatory (M1) macrophages, which acquire anti-tumoral and antimicrobial activity , while exposure to IL-4 and IL-13 favors an anti-inflammatory (M2) macrophage phenotype, which promotes tumor growth and suppression of inflammatory responses. Previous studies of canine polarized macrophages have identified several surface markers that distinguished GM-CSF (granulocyte macrophage colony stimulating factor), IFNg (interferon gamma and LPS (lipopolysaccharide) derived M1 macrophages or M-CSF (macrophage colony-stimulating factor) and IL-4 simulated M2 macrophages; and reported a subset of genes that can be used to differentiate between polarization states. However, the need remains to understand the underlying biological mechanisms governing canine macrophage polarization states. Therefore, in the present study we investigate polarized canine macrophages using transcriptome sequencing, a larger panel of flow cytometry markers, and antimicrobial functional assays. Transcriptome analysis of primary canine monocyte-derived macrophages revealed unique, previously unreported signatures for polarized M1 and M2 macrophages. New flow cytometric markers were also identified, along with a deeper understanding of the influence of macrophage polarization on antimicrobial functions. Taken together, the findings reported here provide additional insight into the functional and transcriptomic changes that canine macrophage undergo in different microenvironments and identify new tools for the evaluation of M1 and M2 macrophages in dogs.